(untitled) (Stato, Chiese e pluralismo confessionale, 2022)
Papers presented at the panel "The spatial ramifications of religion: new and traditional legal challenges " held at the Annual Conference 2022 of EuARe (European Academy of Religion), which took place in Bologna from 20th to 23rd June 2022 and was organised by FSCIRE.